2021
DOI: 10.1038/s41598-020-80816-x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial dynamics in 2-methoxyestradiol-mediated osteosarcoma cell death

Abstract: Osteosarcoma (OS) is one of the most malignant tumors of childhood and adolescence. Research on mitochondrial dynamics (fusion/fission) and biogenesis has received much attention in last few years, as they are crucial for death of cancer cells. Specifically, it was shown that increased expression of the cytoplasmic dynamin-related protein 1 (Drp1) triggers mitochondrial fission (division), which activates BAX and downstream intrinsic apoptosis, effectively inhibiting OS growth. In the presented study, human OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…However, the activity of ATP via purinergic receptors may mediate tumor promoting activities in prostate and breast cancer cells [204,205]. Based on this discovery, we suggest that anticancer mechanism of 2-ME relies on selective nitro-oxidative stress generation controlling the mitochondrial dynamics, including inhibition of biogenesis and induction of mitochondrial fission, finally resulting in mitophagy and cancer cell death [202].…”
Section: Mitochondrial Biogenesis and Mitochondrial Dynamics As Targementioning
confidence: 88%
See 1 more Smart Citation
“…However, the activity of ATP via purinergic receptors may mediate tumor promoting activities in prostate and breast cancer cells [204,205]. Based on this discovery, we suggest that anticancer mechanism of 2-ME relies on selective nitro-oxidative stress generation controlling the mitochondrial dynamics, including inhibition of biogenesis and induction of mitochondrial fission, finally resulting in mitophagy and cancer cell death [202].…”
Section: Mitochondrial Biogenesis and Mitochondrial Dynamics As Targementioning
confidence: 88%
“…In our own studies it has been already demonstrated that 2-ME inhibits mitochondrial biogenesis especially at low physiological concentrations, targeting PGC-1α, COXI, and SIRT3 via nuclear recruitment of nNOS and NO generation [146]. What is more, 2-ME induces DRP-1 expression, leading to inhibition of mitochondrial dynamics and apoptosis of 143B OS cells [202]. The anticancer mechanism of 2-ME and its plausible neurodegenerative features are presented in Figure 1.…”
Section: Mitochondrial Biogenesis and Mitochondrial Dynamics As Targementioning
confidence: 93%
“…The experimental conditions, such as time and doses, were primarily established based on our previous research [ [32] , [33] , [34] ]. The conditions were subsequently optimized according to lung cancer A549 cell line.…”
Section: Methodsmentioning
confidence: 99%
“…2-Methoxyestradiol (2-ME) is a major metabolite of E2. Interestingly, in contrast to its parent compound, it has potent anticancer and antiangiogenic activity as confirmed in several in vitro and in vivo studies [ [2] , [3] , [4] , [5] , [6] , [7] , [58] ]. In our previous research we have established that 2-ME might be potentially used as an effective anticancer agent in therapy of osteosarcoma, neuroblastoma and possibly other solid tumors [ [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation